0543 The association of sleep-disordered breathing and daytime asthma burden among former premature school age children with bronchopulmonary dysplasia. (25th May 2022) - Gunnlaugsson, Sigfus; Mukharesh, Lana; Greco, Kimberly; Petty, Carter; Gaffin, Jonathan
Abstract: Introduction: Sleep-disordered breathing (SDB) and asthma have a bidirectional relationship. Almost half of former premature school age children with bronchopulmonary dysplasia (BPD) have asthma or asthma-like symptoms. Prematurity is a known risk factor for sleep-disordered breathing. However, little is known about the association of SDB and asthma symptoms in former premature school age children with BPD. Methods: Study sample comprised of participants in an ongoing cohort study, the AERO-BPD study. Participants were 6-12 years old, were born < 32 weeks gestational age and had been diagnosed with BPD. We administered the Pediatric Sleep Questionnaire (PSQ) and asthma symptom questionnaires. The prevalence of SDB was determined based on a PSQ > 0.33. The relationship between SDB and daytime asthma symptoms was assessed by multivariate logistic regression, adjusting for sex, race, BMI, rhinitis, asthma controller medication and days on respiratory support in the NICU. Results: There were 33 subjects with a mean age of 8.8 years, roughly half were male and one third were overweight/obese. About half (48.5%) had daytime asthma symptoms and 39.4% had SDB. About half were on controller medication (inhaled corticosteroid or leukotriene receptor antagonist) and 39.4% had rhinitis. Among the 13 subjects with SDB, 11 reported daytime asthma symptoms and 5 of the 20 subjects without SDB reported daytime asthma symptoms. Subjects with SDB had over 17 times the odds of daytime asthma symptoms (OR 17.61, 95% CI [1.23, 251.76], p=0.035) compared to subjects without SDB, while adjusting for sex, race, BMI, rhinitis, controller medications and days on respiratory support in the NICU. Conclusion: Our findings suggest that SDB is highly prevalent among former premature school age children with BPD. The findings suggest a relationship between SDB and daytime respiratory symptom burden among these patients rather than mere co-existence. Support (If Any):